Atomistic MD simulation reveals the mechanism by which CETP penetrates into HDL enabling lipid transfer from HDL to CETP - Geraldine Cilpa-Karhu; Matti Jauhiainen; Marja-Liisa Riekkola (Journal of Lipid Research, 2015)
Inhibition of cholesterol ester transfer protein (CETP), a protein mediating transfer of neutral lipids between lipoproteins, has been proposed as a means to elevate atheroprotective HDL subpopulations and thereby reduce atherosclerosis. However, off-target and adverse effects of the inhibition have raised doubts about the molecular mechanism of CETP-HDL interaction. Recent experimental findings have demonstrated the penetration of CETP into HDL. However, atomic level resolution of CETP penetration into HDL, a prerequisite for a better understanding of CETP functionality and HDL atheroprotection, is missing. We constructed an HDL particle that mimics the actual human HDL mass composition and investigated for the first time, by large-scale atomistic molecular dynamics, the interaction of an upright CETP with a human HDL-mimicking model. The results demonstrated how CETP can penetrate the HDL particle surface, with the formation of an opening in the N barrel domain end of CETP, put in evidence the major anchoring role of a tryptophan-rich region of this domain, and unveiled the presence of a phenylalanine barrier controlling further access of HDL-derived lipids to the tunnel of CETP. The findings reveal novel atomistic details of the CETP-HDL interaction mechanism and can provide new insight into therapeutic strategies.